Ionospheric Disturbance on GNSS Receivers and other systems - Wang, Weihua (My University, 2015)
Equatorial ionospheric plasma irregularities are generated at the magnetic equator areas after sunset due to plasma instabilities. Its impact on the GPS (Global Positioning System) signals, both amplitude and phase, often results in a degraded performance of the GPS receivers. Based on observational data obtained from dual-frequency GPS receivers at two triangular observational networks in south Brazil, ionospheric variability over one full year range (2013) is studied through the Total Electron Content (TEC) distribution. Small-scaled local TEC variations of the region of two observational networks are also presented. From characterization of the local TEC variations, it is thought to be primarily related to the local Equatorial Plasma Bubbles' (EPBs) activities due to the Equatorial Ionospheric Anomaly (EIA).
Keywords: Informations- och kommunikationsteknik; Materialvetenskap; Kommunikationssystem; Signalbehandling; Datorsystem; Information & Communication Technology; Materials Science; Communication Systems; Signal Processing; Computer Systems